PERBANDINGAN SILASE RANSUM KOMPLIT BERBASIS JABON DAN JERAMI UNTUK MENINGKATKAN KETERSEDIAAN PAKAN SAPI PERAH BERKUALITAS SECARA BERKESINAMBUNGAN (Comparison of complete rations silages made on rice straw or maize based for sustainable supply of quality f - TOGAR NAIBAHO; Idat Galih Permana; Despal Despal (Buletin Ilmu Makanan Ternak, 2017)
The present research was aimed to compare two complete ration silages made on rice straw or maize based to increase availability and sustainability of dairy cows feed. This study was conducted in dairy farm area Cibungbulang, Bogor. The experiment was conducted in August 2016 until March 2017. Parameters measured in this experiment were physic, chemical, fermentative and utility characteristics of the silage. The experiment used completely randomized design for fermentative characteristics and randomized block design for utility characteristics with two treatments (R1 and R2), and four replications (as blocks based on the cows initial milk production). All data were analyzed using T-test. Physical characteristics used descriptive statistic. No significantly different data was found between the two based silage. The silage produced in this experiment were very good quality as shown by physical, chemical, fermentative and in vitro utility characteristics. It is concluded that rice straw can be used as based silage as good as maize if it is formulated to match the cow requirement.Key words: rice straw, maize, complete ration silage, dairy.